2022
DOI: 10.1002/nafm.10790
|View full text |Cite
|
Sign up to set email alerts
|

Reservoir Fish Escapement in North America: A Historical Review and Future Directions

Abstract: Downstream escapement of fishes from reservoirs via release structures can represent a loss to populations that is comparable to natural and harvest mortality. Consequently, quantifying and managing fish escapement constitute a

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(30 citation statements)
references
References 82 publications
0
4
0
Order By: Relevance
“…Proliferation of impounded rivers and streams in the past century has led to imperilment of many afected fsh species [2]. One of the more deleterious impacts of dams on native lotic specialists has been impeded movement, including spawning migrations, and has led to population fragmentation [2,3,5,8,[17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…Proliferation of impounded rivers and streams in the past century has led to imperilment of many afected fsh species [2]. One of the more deleterious impacts of dams on native lotic specialists has been impeded movement, including spawning migrations, and has led to population fragmentation [2,3,5,8,[17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…Changing outflow patterns will also affect fish escapement and downstream connectivity (Lewis et al 2022, this special section). Lewis et al's (2022) review indicated that fish escapement from reservoirs during high-water events can be substantial and is species-specific but can also be successfully reduced by retention structures (e.g., fish barrier fences). Fisheries managers face watershed-scale issues that likely fall outside their control (Allen et al 2008), and although they may become increasingly involved in discussions regarding broader basin issues, many times these decisions are made with little regard for reservoir fisheries (Fowler 2008).…”
mentioning
confidence: 99%
“…The prediction of Allen et al (2008) that water use issues in reservoir management were likely to increase has been borne out especially in the U.S. West, where Lake Mead on the Colorado River reached its lowest level ever recorded in July 2022 due to an ongoing historic drought and overallocation of water for agriculture and municipal uses (Udall and Overpeck 2017;Carlowicz 2022). Changing outflow patterns will also affect fish escapement and downstream connectivity (Lewis et al 2022, this special section). Lewis et al's (2022) review indicated that fish escapement from reservoirs during high-water events can be substantial and is species-specific but can also be successfully reduced by retention structures (e.g., fish barrier fences).…”
mentioning
confidence: 99%
See 2 more Smart Citations